Evolusi Pertukaran dalam Strategi Pemasaran - Iqbal, M. Ali (Lembaga Penerbitan Unversitas Esa Unggul, 2014)
AbstractExchange is a useful framework for conceptualization in marketing behavior. The recent objective marketing is not only creating in selling products or services and customer satisfaction needing but also the objective has been moving to creating and integrating customer value. Satisfaction, trust and commitment attributes have been used as attributes for creating customers value. Drawing on insight from extant literature this article purpose analysis of evolusion exchange in marketing strategy. The qualitative research is used in this study by using several literatures. The author found that there was a change in exchange paradigm from transactional to relational exchange. The moving of paradigm as parallel with the development of world economy especially in the post industry era.Keywords: relationship marketing, longlife customers value, relational exchange